Occurrence of a new disease of irrigated cotton, in Brazil, caused by Sclerotinia Sclerotiorum - Charchar, Maria José D´Avila; dos Anjos, José Riibamar Nazareno; Ossipi, Ewerton (Pesquisa Agropecuaria Brasileira, 1999)
In 1996, a new disease caused by Sclerotinia sclerotiorum (Lib.) de Bary was observed on cotton (Gossypium hirsutum L.) Deltapine cultivar irrigated under central pivot at Paracatu, MG, in the Savana region of Central Brazil. The symptoms were wilt, necrosis and rot. White mycelium and black sclerotia developed inside the boll. The pathogenicity test was done with two-week old cotton seedling cultivars Deltapine and IAC 22 and bean and okra seedlings. The plants were incubated at high humidity for 48 hours at 25oC. Three days after inoculation, severe symptoms of wilt and necrosis were observed. S. sclerotiorum was reisolated from the damaged plant tissues, and Koch´s postulates were completed. This is the first report of S. sclerotiorum natural occurrence on cotton in Brazil.